SARS-CoV-2 Vaccine Development: Current Status (2020)
In the midst of the SARS-CoV-2 pandemic and its attendant morbidity and mortality, safe and efficacious vaccines are needed that induce protective and long-lived immune responses. Over 120 vaccine candidates worldwide are in various preclinical, and phase I-III clinical trials that include inactivated, live attenuated, viral vectored replicating and non-replicating), protein and peptide-based, and nucleic acid approaches. Vaccines will be necessary both for individual protection and for the safe development of population-level herd immunity. Public-private partnership collaborative efforts, such as the Accelerating COVID-19 Therapeutic Interventions and Vaccines (ACTIV) mechanism, are key to rapidly identifying safe and effective vaccie candidates as quickly and efficiently as possible. In this article, we review the major vaccine approaches being taken and issues that must be resolved in the quest for vaccines to prevent COVID-19. We scanned the PubMed database from 1963–2020 for all publications using the following search terms in various combinations: SARS, MERS, COVID-19, SARS-CoV-2, vaccine, clinical trial, coronavirus, pandemic, vaccine development. We also did a web search for these same terms. We also examined the World Health Organization, Centers for Disease Control and Prevention, and other public health authority websites. We excluded abstracts and all articles that were not written in English.